Parliament and political pamphleteering in fourteenth-century England - Oliver, Clementine (York Medieval Press, 2010)
First full examination of the phenomenon of the medieval political pamphlet. Some sixty years before the advent of the printing press, the first political pamphlets about parliament circulated in the city of London. Often vitriolic and satirical, these handwritten pamphlets reported on a trilogy of parliamentary victories against the crown known as the Good, the Wonderful, and the Merciless Parliaments. The first pamphlets point to the existence of a market of readers hungry for news of parliament as well as to the emergence of public opinion as a political force. This book reconstructs the lives of the political pamphleteers as well as the political landscape of late fourteenth-century England, giving particular emphasis to the large group of bureaucrats living in London to which Geoffrey Chaucer belonged. Dr Clementine Oliver is Associate Professor of History at California State University.